Potential application of vacuum insulated tubing for deep borehole heat exchangers. (September 2018) - Śliwa, Tomasz; Kruszewski, Michał; Zare, Alireza; Assadi, Mohsen; Sapińska-Śliwa, Aneta
Highlights: Borehole Heat Exchanger is one of the best possible ways to utilise geothermal heat. Abandoned or negative wells can be reconstructed for Deep Borehole Heat Exchangers. Vacuum Insulated Tubing creates efficient geothermal system at greater well depths. Vacuum pipes significantly decrease thermal conductivity coefficient of inner column. Abstract: During recent Paris climate agreement, 195 courtiers pledged to reduce the greenhouse gas emissions and pursue effects to limit the global temperature increase to 2 °C. Geothermal resources, as renewable sources of energy, can contribute to electricity, as well as heat production without having any negative impacts on environment or the security of energy supply. One of the ways to extract geothermal heat from the Earth's crust are Deep Borehole Heat Exchangers, which can be either drilled especially for such purposes or, what is more cost effective, reconstructed from already existing, negative or abandoned oil or natural gas wells. In many depleted boreholes, exploiting underground geothermal waters is impossible or technically complex, therefore potential reconstruction for heat exchanger might be the only possible solution that allows utilizing geothermal heat. Polish energy sector is heavily dependent on coal resulting in large CO2 emission per capita. The country has considerable potential for geothermal energy development, as there are large numbers of deep and abandoned wells that might be utilized for geothermal heat production. Following paper investigates potential reconstruction of abandoned or negative wells into deep coaxial borehole heat exchangers. Main focus was put on selection of coaxial inner column which enables for heat carrier circulation. To maximize the heat uptake from geothermal systems based on borehole heat exchangers, it is advised to use inner column made from material with lowest possible thermal conductivity coefficient. Vacuum Insulated Tubing, as one of the options of insulated inner column, can significantly improve heat production and increase efficient energy use. This technology found plethora of applications in offshore and onshore petroleum industry and is yet to gain more popularity within geothermal sector.